THE STUDY OF THE IMPACT OF AMALGAMATION OF THERAPIST EMBODIMENT AND CLIENTS PERCEPTION OF THERAPIST ON THERAPEUTICALLIANCE OUTCOME - Naveed Shibli; Sajida Anwer (International Journal of Contemporary Issues in Social Sciences, 2024)
Therapeutic alliance is a gateway to therapy outcome is known and established but how do amalgamations of therapist’s embodiment feel and client’s perception of the therapist appearance could make the therapeutic alliance beginning a better means to an end was the question that made the researchers to conduct the present study with 70 clients on their routine visits to an OPD of a hospital for clinical psychologist assistance and the therapist received each ten of those in single dress and used seven dress codes (embodiment), usual or remote to know the effect of by these on the session ratings performed by the clients on SRS. The results support the varied impact of various amalgamations.